Stegoelmis Hinton, 1939 (Coleoptera: Elmidae: Elminae) in Brazil: two new species and a key to the Brazilian species - Fernandes, André S.; Passos, Maria Inês S.; Hamada, Neusa (Zootaxa, 2011)
Two new species of the genus Stegoelmis Hinton, 1939, S. figueiredoensis sp. nov. from Amazonas State, Brazil and S. shepardi sp. nov. from Roraima State, Brazil and Saint Laurent Du Maroni, French Guiana, are described and illustrated based on adult specimens. This work also provides a taxonomic key to males of Stegoelmis species known from Brazil.